Microelectromechanical Systems (MEMS) 1996
DOI: 10.1115/imece1996-1365
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Shape Memory Alloy Microactuators

Abstract: Thin film shape memory alloys (SMAs) have the potential to become a primary actuating mechanism for mechanical devices with dimensions in the micron to millimeter range requiring large forces over long displacements. In this paper, the thermo-mechanical behavior of shape memory films is presented, techniques for characterizing Ni-Ti-based shape memory films are evaluated, and design issues for SMA microactuators are discussed. The substrate curvature method is used to investigate the response of Ni-Ti-Cu SMA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Advances in microelectromechanical (MEMS) technology have led to several attempts to develop micro-scale biopsy tools. Lee et al [5] fabricated a micro-gripper using deposition of shape memory alloy (SMA) on silicon substrates and Krulevitch et al [6,7] reported micro-fabricated instruments for micro-biopsy and precision cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in microelectromechanical (MEMS) technology have led to several attempts to develop micro-scale biopsy tools. Lee et al [5] fabricated a micro-gripper using deposition of shape memory alloy (SMA) on silicon substrates and Krulevitch et al [6,7] reported micro-fabricated instruments for micro-biopsy and precision cutting.…”
Section: Introductionmentioning
confidence: 99%